Effects of TLR agonists on the hypoxia-regulated transcription factor HIF-1alpha and dendritic cell maturation under normoxic conditions. - Rolf Spirig (Public Library of Science (PLoS), 2010)
Dendritic cells (DC) are professional antigen presenting cells that represent an important link between innate and adaptive immunity. Danger signals such as toll-like receptor (TLR) agonists induce maturation of DC leading to a T-cell mediated adaptive immune response. In this study, we show that exogenous as well as endogenous inflammatory stimuli for TLR4 and TLR2 induce the expression of HIF-1alpha in human monocyte-derived DC under normoxic conditions. On the functional level, inhibition of HIF-1alpha using chetomin (CTM), YC-1 and digoxin lead to no consistent effect on MoDC maturation, or cytokine secretion despite having the common effect of blocking HIF-1alpha stabilization or activity through different mechanisms. Stabilization of HIF-1alpha protein by hypoxia or CoCl(2) did not result in maturation of human DC. In addition, we could show that TLR stimulation resulted in an increase of HIF-1alpha controlled VEGF secretion. These results show that stimulation of human MoDC with exogenous as well as endogenous TLR agonists induces the expression of HIF-1alpha in a time-dependent manner. Hypoxia alone does not induce maturation of DC, but is able to augment maturation after TLR ligation. Current evidence suggests that different target genes may be affected by HIF-1alpha under normoxic conditions with physiological roles that differ from those induced by hypoxia.